EEG signals during epileptic seizure as a semigroup of upper triangular matrices - Binjadhnan, Faisal A. M. (Science Publications, 2010)
Problem statement: EEG signals during epileptic seizure can be presented as an algebraic structure, namely semigroup of upper triangular matrices. Approach: EEG signals during seizure were recorded and composed into set of matrices. They were transformed into upper triangular matrices using QR-Schur decomposition and finally as a semigroup of upper triangular matrices. Results: EEG signals during epileptic seizure were transformed as a semigroup of upper triangular matrices under matrix multiplication. Conclusion: This study described the procedure to transform signal during epileptic seizure (brainstorm) into an algebraic structure. This is the key step that will enable us to further proceed to obtain some pattern out of the seizure data in our future research.